A Prospective Observational Case Series of Liver Injury in Paediatric Patients Secondary to Consumption of Ayurvedic Herbomineral Formulations. - Rekha V. Shinde1, Ranjit Ambad2, Sunanda C. Patil3, Parag Aradhey4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Ayurvedic medicines especially herbomineral formulations are combinations of metalsand herbs but not in a raw form. There are very good positive things in society about these herbomineralmedicines and lots of misconceptions in modern world and modern scientist. They are much confusedthat how ayurvedic doctors can use metals in medicines; because they feel that metals are toxic to humanbody, metal can cause hepatotoxicity and nephrotoxicity. This is on scientific level totally confusion andmisunderstanding in the mind of allopathy people. Why this confusion arises…? Actually they must littlebit understand about ayurvedic science. This science never suggests to use these metals in the raw form.They are converting these metals totally nano particle level so original metal has been lost its molecularstructure and it is completely new ayurvedic bhasmas are only oxides of metal. First purify the metal andafter purification with lots of complicated biochemical processing, converting them into such moleculethat molecule does not have a single raw metal molecule. This must be understood that final product iscompletely different than raw metal used. If try to study this things then nobody will challenge to ayurvedicscience.Aim: Observe the incidence of hepatic injury in paediatric patients due to herbomineral drug consumption.Material and Method: In this prospective case series 5 drugs regimen of herbomineral medicine was givento 14 paediatric patients of age group 4 years to 14 years who were diagnosed as reactive and recurrentrespiratory disease. The total duration of drug delivery was 90 days. After successful completion of treatmentcourse Liver Function Test (LFT) of each patient was done and conclusion was drawn.Outcomes: Total 14 patients, biomarkers of Liver Function Test were observed normal and at last follow upevery patient was clinically fine.Conclusion: Use of herbomineral medicines in paediatric patients is safe and it does not cause hepatotoxicity